Anime-Style Illustrator Adaptation in Penetrating the Virtual Art Market - Alsya Epi Elizabeth; Thayaba Apta Cheda Prima; Tri Intan Novianti; Septania Dwi Novanty (Journal of Interdisciplinary Social Sciences and Humanities, 2025)
Illustrators often struggle with recognition and income stability in the competitive virtual market. This article examines how they adapt to popular trends, such as anime-style art, and the marketing strategies they employ to achieve financial success. The research utilizes surveys, interviews with selected illustrators, and participatory observations within creative communities. This methodology aims to provide a deep understanding of how illustrators build networks, adapt to shifting trends, and navigate challenges like intense competition and fluctuating demand. Ultimately, this study is designed to offer valuable insights and practical strategies, helping illustrators understand effective marketing patterns and overcome virtual market challenges. The goal is to empower them to become more confident and adaptive in their pursuit of success.